Pengaruh Likuiditas, Ukuran Perusahaan, Dan Kepemilikan Saham Publik Terhadap Pengungkapan Laporan Keuangan - Nova Fitriah (2021)
This study aims to determine the effect of liquidity, firm size, and public share ownership on financial statement disclosure on campanies in property & real estate listed on the Indonesia Stock Exchange for the 2017-2019 period. This study uses quantitative research methods with secondary data in the form of reports obtained from the Indonesia Stock Exchange page or the company's website. This study consisted of a total sample of 95 annual report property & real estate companies. The sampling technique used is purposive sampling. The technique used in this study is multiple linear regression with SPSS 25. The results of this study indicate that (1) Liquidity has no effect on financial statement disclosure, (2) firm size has a significant positive effect on financial statement disclosure, and (3) Public share ownership has no effect on financial statement disclosure.